"She is the one who knows": A qualitative exploration of oral and injectable PrEP as part of a community empowerment approach to HIV prevention among female sex workers in the Dominican Republic and Tanzania. - Andrea Mantsios; Ohvia Muraleetharan; Yeycy Donastorg; Martha Perez; Hoisex Gomez; Catherine Shembilu; S Wilson Beckham; Tahilin Sanchez Karver; Wendy Davis; Samuel Likindikoki; Jessie Mbwambo; Clare Barrington; et al. (Public Library of Science (PLoS), 2022)
Despite documented interest among female sex workers (FSW), uptake of oral pre-exposure prophylaxis (PrEP) for HIV prevention has been low. Recent trials and regulatory approval of long-acting injectable (LAI) PrEP offer new hope for the potential of this biomedical intervention. We examined FSW's PrEP-related interest and preferences regarding both oral and LAI PrEP situating these dynamics within their specific social and occupational realities. We conducted this work using qualitative methods across two distinct contexts by conducting 40 in-depth interviews with FSW in Tanzania and the Dominican Republic. Textual data was coded using iterative thematic content analysis. Analytic summaries were developed and reviewed to identify recurring themes. We systematically organized themes within each country and then compared across settings. Women in both settings expressed strong interest in PrEP seeing it as an important option to protect themselves in their work. Most participants preferred LAI PrEP due to expectations of reduced stigma and concerns about daily pill adherence and side effects. Occupational factors such as alcohol use, overnight dates with clients, and fear of violence from clients were identified as barriers to daily oral PrEP. LAI PrEP was seen as having the potential to reduce stress related to oral PrEP. Women who preferred pills discussed fear of needles, skepticism about the injections, and others relayed that taking a daily pill would not be challenging for them. There was a pre-dominant sentiment that women know best whether they are better suited for oral or LAI PrEP. Participants stressed the importance of FSW understanding both options to ensure informed decision-making around PrEP and described community-led peer education as key to delivering trusted information. Community empowerment approaches led by FSW which address structural and psychosocial constraints and promote safe work environments may facilitate equitable access and uptake of PrEP among FSW across settings.